On the causes and consequences of divorce - Alessandro Balestrino; Cinzia Ciardi; Claudio Mammini (Center for Economic Studies and ifo Institute (CESifo), 2008)
In most Western economies, the flourishing of the Welfare State has coincided with a decline of the role of the family: divorce has been introduced, and the number of marriages has decreased. We suggest that a taboo against divorce was part of the informal safety net in a period when social protection was provided by the family. Once the State started offering suitable alternatives, the taboo was no longer expedient, and was dropped. For the same reasons, marriage has become less popular. We further notice that divorce is an extremely costly process, and once allowed it may act as an independent reason for the reduction of the number of marriages. This latter result is especially evident under the assumption that agents subjectively evaluate the probability of facing a divorce using an availability heuristic.
Keywords: J12; D10; D70; D81; 330; Divorce; marriage; availability heuristic; Scheidung; Ehe; Familienökonomik; Sozialstaat; Sozialhilfe; Theorie; Westliche Staaten